Changes in Epidemiology of Acetaminophen Overdoses in an Urban County Hospital After 20 Years. (5th August 2022) - Long, Apple; Magrath, Melissa; Mihalopoulos, Meredith; Rule, Jody A.; Agrawal, Deepak; Haley, Robert; Kleinschmidt, Kurt; Lee, William M.
Abstract : INTRODUCTION: Acetaminophen (APAP) toxicity is the main cause of acute liver failure in the United States. A prior series (1992–1995) identified 71 hospitalized adults with APAP toxicity through the International Statistical Classification of Disease and Related Health Problems, 9th revision (ICD-9) code at Parkland Hospital, Dallas, TX. METHODS: We used a laboratory database search of serum APAP levels from 2011 to 2015 to identify patients with APAP toxicity in the same hospital. RESULTS: We identified 140 patients hospitalized for APAP toxicity from 27, 143 APAP levels obtained; 35 required Intensive Care Unit (ICU) admission, and there were no deaths. APAP toxicity/100, 000 admissions was similar between eras. DISCUSSION: APAP toxicity continues unabated after 20 years but with improved overall outcomes.